The role of oxidative stress in atherosclerosis: the hope and the hype. - Runge, M. S. (American Clinical and Climatological Association, 1999)
Numerous lines of investigation support the importance of oxidative stress in the development of atherosclerosis. Results from studies in isolated cells and in animal models of atherosclerosis are compelling, as are those from a select number of clinical trials. Unfortunately, the results of prospective, randomized clinical studies have been disappointing and may reflect our current inability to accurately assess oxidative risk and the response to antioxidant therapy. Only when it is possible to accurately and easily measure oxidative stress will it be possible to accurately determine the efficacy of different antioxidant approaches.